The Effect of Physical Exercise and PETTLEP Mental Imagery (Constant and Variable) on Learning Basketball Free Throw Task - Mohammad Naderi; Alireza Bahrami; Darius Khajavi (University of Tehran, 2017)
.The targeted 75 patients with a score of 45- 55 imagery and had no history of basketball free throw were selected and were divided in 5 groups, each of 15; control, mental imagery PETTLEP Constant, group mental imagery PETTLEP Constant combined with physical exercise Constant, group imagery PETTLEP of the variable, group mental imagery PETTLEP variable combined with physical exercise variables. To collect data was used in the Movement Imagery Questionnaire - Revised (MIQ-R).At first of all groups were taken pre-test of basketball free throw. Exercise protocol, eight sessions were conducted for eight days. At the end, taken post-test. After Data normality and equality of variances, The result have been surveyed by analysis of variance, Tukey test and also the 16 version of SPSS in P value of P